On the Capacity of MIMO Channels and Its Effect on Network Performance - Luccini, M.; Primak, S.; Shami, A. (2008 3rd International Conference on Information and Communication Technologies : from Theory to Applications : Damascus, Syria 7-11 April 2008, 2008)
In multiple antenna wireless systems (MIMO), the channel capacity can be modeled as a Gaussian random process under certain conditions. Channel capacity outages introduce a probability of data loss at the physical layer. Accounting for such effects on the network design requires a cross-layer approach, which involves joint consideration of physical (PHY) and upper layer performances (i.e. Medium Access Control layer, MAC). In this paper, we consider a single buffer queuing system subject to a buffer overflow probability. The total failure probability for the system is defined as the sum of the probability of data loss due to buffer overflows and the probability of no reliable transmissions due to channel capacity outages. We show that a joint consideration of the errors in transmission is necessary and opens new issues in the system design, in terms of the optimal service rate and buffer size.